Article Review: Organic Solar Cell - Gultom, Noto Susanto; Azka, Muhamad Fauzan; Khoir, Irfansyah; Hashifa, Chisa; Nurasiah, Nurasiah; Iskandar, Johan; Nurhilal, Otong (Universitas Padjadjaran, 2025)
One of the emerging technologies that has gained attention as an alternative for meeting renewable energy demands is the Organic Solar Cell (OSC). OSC is a type of photovoltaic device that utilizes organic electronic materials. The fundamental operating principle of OSC is based on the Highest Occupied Molecular Orbital (HOMO) and the Lowest Unoccupied Molecular Orbital (LUMO), with organic compounds serving as the active materials, enabling the conversion of light energy into electricity. Research on OSC has continuously evolved over the years to achieve optimal performance. The substrate/transport layer, which serves as the foundation for the organic active layer in OSC, can be categorized into several types, including ITO-based OSC, conducting polymer-based OSC, silver nanowire-based OSC, metal-based OSC, and graphene-based OSC. Organic solar cells offer several promising prospects, such as relatively low production costs, as well as flexible and transparent design features. However, OSCs also face several challenges, including relatively low efficiency and environmental stability concerns. Addressing these challenges is crucial to unlocking the full potential of OSC technology. This article first provides a general overview of OSC advancements, followed by a summary and analysis of its working principles, performance parameters, and structural components. Finally, we explore recent breakthroughs in OSC development in detail.